Morphological Characterization of Yardlong Bean for Pod Borer Infestation - Nasrin Jahan Sultana; Krishna Rany Das; Md. Abdullah Al Masum; Masum Ahmad (Fundamental and Applied Agriculture)
In order to assess the resistance of several yardlong bean types to pod borer attacks, an experiment was conducted at the experimental farm of Bangladesh Agricultural University, located in Mymensingh, Bangladesh, from September 2022 to April 2023. The study included nine different varieties. The study included nine different varieties. The experiment was arranged with five replications using a completely randomized design (CRD). Among the various yardlong bean varieties utilized in this study, BARI Borboti-2 produced the highest yield of 98.57g per plant. A comparison of the BARI Borboti-2 variety's dry seed output and other characteristics showed that it had the highest total number of pods per plant (8.40), the lowest infestation rate (13%), and the maximum quantity of dry seeds (15g). In most cases, the Lubna variety had the worst performance. The majority of the types had the second lowest infection rate. According to the current investigation, BARI Borboti-2 showed the best performance. The local variety BARI Borboti-2 demonstrated better overall performance in terms of yardlong bean morphology during the cultivation period, with fewer pod borer infestations, according to the study. Out of the nine cultivars studied, BARI Borboti-2 and Ufshi had the best yield and showed resistance to pod borer infestation. [Fundam Appl Agric 2024; 9(4.000): 277-282]